Whole genome analysis of Neisseria meningitidis isolates from invasive meningococcal disease collected in the Czech Republic over 28 years (1993-2020) - Honskus, Michal; Krizova, Pavla; Okonji, Zuzana; Musilek, Martin; Kozakova, Jana (PLoS One, 2023)
Invasive meningococcal disease belongs among the most dangerous infectious diseases in the world. Several polysaccharide conjugate vaccines against serogroups A, C, W and Y are available and two recombinant peptide vaccines against serogroup B (MenB vaccines) have been developed: MenB-4C (Bexsero) and MenB-fHbp (Trumenba). The aim of this study was to define the clonal composition of the Neisseria meningitidis population in the Czech Republic, to determine changes in this population over time and to estimate the theoretical coverage of isolates by MenB vaccines. This study presents the analysis of whole genome sequencing data of 369 Czech N. meningitidis isolates from invasive meningococcal disease covering 28 years. Serogroup B isolates (MenB) showed high heterogeneity and the most common clonal complexes were cc18, cc32, cc35, cc41/44, and cc269. Isolates of clonal complex cc11 were predominately serogroup C (MenC). The highest number of serogroup W isolates (MenW) belonged to clonal complex cc865, which we described as exclusive to the Czech Republic. Our study supports the theory that this cc865 subpopulation originated in the Czech Republic from MenB isolates by a capsule switching mechanism. A dominant clonal complex of serogroup Y isolates (MenY) was cc23, which formed two genetically quite distant subpopulations and which showed constant representation throughout the observed period. The theoretical coverage of isolates by two MenB vaccines was determined using the Meningococcal Deduced Vaccine Antigen Reactivity Index (MenDeVAR). Estimated Bexsero vaccine coverage was 70.6% (for MenB) and 62.2% (for MenC, W, Y). For Trumenba vaccine, estimated coverage was 74.6% (for MenB) and 65.7% (for MenC, W, Y). Our results demonstrated sufficient coverage of Czech heterogeneous population of N. meningitidis with MenB vaccines and, together with surveillance data on invasive meningococcal disease in the Czech Republic, were the basis for updating recommendations for vaccination against invasive meningococcal disease.
Keywords: Antigens, Bacterial; vakcinace; Humans; meningokokové infekce; Neisseria meningitidis séroskupiny B; Vaccination; syntetické vakcíny; Neisseria meningitidis, Serogroup B; Whole Genome Sequencing; antigeny bakteriální; lidé; Serogroup; Meningococcal Infections; séroskupina; Meningococcal Vaccines; sekvenování celého genomu; Czech Republic; Česká republika; meningokokové vakcíny; Vaccines, Synthetic; Neisseria meningitidis